Penyelesaian Sengketa Tanah Harta Pusako Tinggi Terhadap Ahli Waris Yang Punah Melalui Niniak Mamak Nan Salapan Di Nagari Ampalu Kabupaten Lima Puluh Kota - Sonanda, Rahmi; Syuriani, Syuriani; Nazar, Jazman (Law, Development and Justice Review, 2023)
This study aims to find out how to resolve land disputes over the heirs who are extinct through Niniak Mamak Nan Salapan in Nagari Ampalu, Lima Puluh Kota District. In Minangkabau, it is not actually known that there are heirs who are extinct for inheritance, but what is meant here is when the principal or core offspring of a people is gone and the existing inheritance will be passed on to other people who are entitled to the inheritance. This research is descriptive with the type of Juridical Empirical legal research. The author conducts research sociologically, in a field manner where we will examine legal provisions regarding settlement of land disputes over the Pusako Tinggi property if the principal successor is no longer directly present in the life of the Minangkabau people in Jorong Mangunai Tinggi, Kenagarian Ampalu. The results of the research are in the form of a way of resolving legal community disputes in Jorong Mangunai Tinggi using customary regulations that prioritize deliberation so as to produce decisions that are in accordance with customary regulations in the customary law area of Jorong Mangunai Tinggi. In accordance with the field facts obtained by the author, the role of the Ninak Mamak Nan Salapan institution is part of KAN and the results of decisions issued by the Niniak Mamak Nan Salapan institution are submitted to KAN through a regulatory process so that the decision is considered in accordance with existing laws and regulations.